IMPROVED CEMENT RHEOLOGY FOR CEMENTING OPERATION - PATTINASARANY, ADRIAN (2014)
Research has been done to improve cement rheology during oil/gas well cementing operation. Method commonly used to find rheology in term of shear stress, friction pressure and ECD from American Petroleum Institute assumed the cement slurry would exhibit time independent nature. This assumption is disregarding the flow properties after the cement has thickened up due to hydration and resulted lower shear-stress result at high shear-rate and at high time interval. New method has been developed to include the effect of consistency change in calculating the shear-stress, friction pressure and ECD of cement slurry. This method is applicable to calculate shear-stress for oil/gas well cementing job that has negligible free fall effect and pumped at below turbulence rate inside a concentric annulus. This research had combined methods from API Recommended Practice 10A and 10B to achieve research objectives. Research was accomplished using viscometer and consistometer and there were no addition or modification in the components of the devices. Statistical analysis was done to determine fluid model used to calculate the shearstress. Charts were presented for graphical analysis of test results to determine the fluid models. Cement slurry consistency was found to have significant effects to viscosity and ECD. Result from experiments shown that there was increasing in shear-stress due to increase in consistency and at 70 minute there was 61% increase in friction pressure and there was 129.8% increase at 75 minutes and also at 70 minute there was 1.51% increase in ECD and there was 3.95% increase at 75 minutes.